Getting off on the wrong foot? How community groups in Zimbabwe position themselves for partnerships with external agencies in the HIV response - Skovdal, Morten (Global Health, 2017)
BACKGROUND: Partnerships are core to global public health responses. The HIV field embraces partnership working, with growing attention given to the benefits of involving community groups in the HIV response. However, little has been done to unpack the social psychological foundation of partnership working between well-resourced organisations and community groups, and how community representations of partnerships and power asymmetries shape the formation of partnerships for global health. We draw on a psychosocial theory of partnerships to examine community group members’ understanding of self and other as they position themselves for partnerships with non-governmental organisations. METHODS: This mixed qualitative methods study was conducted in the Matobo district of Matabeleland South province in Zimbabwe. The study draws on the perspectives of 90 community group members (29 men and 61 women) who participated in a total of 19 individual in-depth interviews and 9 focus group discussions (n = 71). The participants represented an array of different community groups and different levels of experience of working with NGOs. Verbatim transcripts were imported into Atlas.Ti for thematic indexing and analysis. RESULTS: Group members felt they played a central role in the HIV response. Accepting there is a limit to what they can do in isolation, they actively sought to position themselves as potential partners for NGOs. Partnerships with NGOs were said to enable community groups to respond more effectively as well as boost their motivation and morale. However, group members were also acutely aware of how they should act and perform if they were to qualify for a partnership. They spoke about how they had to adopt various strategies to become attractive partners and ‘supportable’ – including being active and obedient. CONCLUSIONS: Many community groups in Zimbabwe recognise their role in the HIV response and actively navigate representational systems of self and other to showcase themselves as capable actors. While this commitment is admirable, the dynamics that govern this process reflect knowledge encounters and power asymmetries that are conditioned by the aid architecture, undermining aspiring efforts for more equitable partnerships from the get-go.